A A Progressive Criminal Law View Regarding Criminal Liability In Robotic Crimes - Mas Tri Wulandari Ni Gusti Agung Ayu (VYAVAHARA DUTA, 2023)
The Industrial Revolution 4.0 era has produced many advanced technological innovations. One of the results of advanced technology resulting from the Industrial Revolution 4.0 which is widely used in Society 5.0 is robotic technology. Apart from the trend of using robots and their positive impacts, robots can also have negative impacts. Robots can be a tool, even a perpetrator of crime. This research will focus on the progressive criminal law view of criminal liability in robotic crimes. The results of this research are that three accountability approaches can be applied, namely through proportional, strict and direct liability. Through a clear legal framework regarding criminal liability resulting from robot crimes, the law becomes responsive to developments in the current era. Apart from that, the law can also function as "social engineering" in that it encourages legal entities or AI makers to be more careful and careful in building systems so that the AI ​​system which is an important basis for making robots does not cause robots to act in ways that can attack, injure, or endanger other parties.